Power and subjectivity: Making sense of sexual consent among adults living in Sweden. Issue 2 (3rd April 2021) - Linander, Ida; Goicolea, Isabel; Wiklund, Maria; Gotfredsen, Anne; Strömbäck, Maria
ABSTRACT: While sexual consent has been a hot topic during recent years in the Swedish context, there is a lack of empirical studies on the issue. The aims of this study were to analyse how adults in Sweden experience and make sense of sexual (non)consent in sexual encounters, and to contribute to a conceptual discussion of 'sexual consent', especially in relation to a Foucauldian understanding of power and subjectivity. The analysis is based on 31 interviews with adults living in Sweden. Participants describe consenting to sex due to being exposed to interpersonal forms of power, ranging from violence and clear violations of consent to nagging and being subjected to pressure from others. But they also feel pressure and give consent to sex based on self-regulation and disciplinary forms of power, connected to normative ideals about 'the good relationship', monogamy and heterosexuality, men and women, and age. Our Foucauldian analytical lens allowed us to explore and challenge understandings of autonomous, rational subjects who communicate consent on the basis of authentic feelings. It also provided an analytical strategy for analysing and understanding the complex power relations that matter in the negotiation of sexual consent.